Green Extraction of Cherry Flowers (Muntingia calabura L.) and Antioxidant Activity by Ferric Reducing Antioxidant Power Method - St Maryam; Muzakkir Baits; Nabilah Najla (Pharmaceutical Reports, 2026)
The cherry plant (Muntingia calabura L.) is known as a versatile medicinal plant, with its leaves, fruits, and flowerstraditionally used for various therapeutic purposes. This plant contains several bioactive compounds, including flavonoids, tannins, triterpenes, saponins, and polyphenols, which play a crucial role in its antioxidant activity. The present study aimed to determine the antioxidant activity level of Muntingia calabura L. using the Ferric Reducing Antioxidant Power (FRAP) method. The ethanol extract of cherry plant material was obtained using the Microwave-Assisted Extraction (MAE) technique, which had been previously optimized to achieve the highest flavonoid yield through variations in temperature and extraction time, employing a green solvent system. The antioxidant activity was measured by the FRAP method, and the absorbance was recorded using a UV– Visible spectrophotometer at a wavelength of 715 nm. The results were expressed as milligrams of quercetin equivalent per gram of extract (mg QE/g) based on the absorbance data. The antioxidant activity values of the ethanol extract from three replications were 908.56 mg QE/g, 910.6 mg QE/g, and 955.5 mg QE/g, respectively, with an average value of 924.88 mg QE/g extract. These findings indicate that Muntingia calabura L. exhibits strong antioxidant potential, likely attributed to its high flavonoid and polyphenol content, and therefore has promising applications as a natural antioxidant source in traditional and modern medicine.